Case report: Two heterozygous pathogenic variants of CYP24A1: A novel cause of hypercalcemia and nephrocalcinosis in adulthood - Brunerova, Ludmila; Remes, Ondrej; Zoubkova, Veronika; Votypka, Pavel (Frontiers in Medicine, 2023)
Background/Aims: Vitamin D 24-hydroxylase is enzyme, encoded by CYP24A1 gene, which inactivates active vitamin D form to inactive metabolites. More than 20 currently described pathogenic variants (usually biallelic) of this gene are responsible for idiopathic infantile hypercalcemia manifested typically in childhood (often in newborns) with hypercalcemia, hypercalciuria and nephrocalcinosis. However, a few patients (mostly with monoallelic heterozygous pathogenic variant) can develop mild symptoms in adulthood. Case description: We present the case of 43-year old male patient with hypertension and heterozygous Leiden mutation, with mural thrombi in the common iliac artery who was sent by nephrologist to endocrinological examination due to hypoparathyroidism, progressive hypercalcemia, hypercalciuria and CKDG2A1. Complete laboratory and imaging methods (including PET-CT) excluded PTH-related peptide-mediated hypercalcemia and granulomatosis. Finally, the genetic analysis of CYP24A1 gene revealed the presence of a novel combination of two heterozygous pathogenic variants: CYP24A1: c. 443T>C p.(Leu148Pro) and c.1186C>T p.(Arg396Trp). Conclusion: Differential diagnosis of patients with hypercalciuria, nephrocalcinosis and hypercalcemia related to vitamin D exposure should include CYP24A1 gene mutation. To our knowledge, this is the first case of the novel combination of two heterozygous pathogenic variants of CYP24A1.